Qualificational differences in the structure of archery training on different stages of long-term training - Brisky, Y.; Pityn, M.; Antonov, S.; Vaulin, O. (Journal of Physical Education and Sport, 2014)
Safe regimens are a pre-requisite for children and youths who exercise and train in the hot and humid weather Archery by the structure of competitive activity belongs to the group of high coordinated kind of sports. By direction the technique is oriented on achieving maximal metric result which demands the concern of specific principle of sport training of unity and cooperation of competitive and training activity, perfect formation of movement habits. According to this must be defined the leading value of technical training in the structure of long-term archery sportsmen improvement program.